Czech Bluegrass in Play - Bidgood, Lee (Lidé města, 2015)
Drawing from scholarship on play, ritual, and performance, I propose that Czech bluegrass thrives – as does my fieldwork – in a state of in-betweenness, in a territory that is between work, play, here and there, self and other. Being comfortable with this kind of in-between state is important for fieldwork, and for music-making – play, I find, is both a central activity and metaphor in both. The bluegrass play I discuss in this essay can become a response to the encroachment of Americanization in economic and cultural globalization, but also a way of being “Americanist” – and entirely Czech.